TSD Algorithm to Design CA Based Expert System for Pipelining to Stop Urban Flood - Kumar, Neeraj; Arora, Geeta; Agrawal, Alka; Ahmad Khan, Raees (International Journal of Engineering and Technology, 2018)
Flood is a frequent disaster disturbing the daily life and sometimes found deadly. Out of all kind of floods, urban flood is avoidable through quick exit of drainage. Urban flood starts water logging that can be eliminated by efficient pipeline structure. A dedicated drainage pipeline structure may facilitate better during urban flood.Â  A Cellular Automata is a theoretical computer science tool used to solve complex problems as well as to design structures. In these days, applications of CA continuously increasing, out of which an application of designing a flood avoidance drainage mechanism using CA based structure presented in this paper. To generate knowledge for an expert system to design a flood free city in initial stage of development of a city this paper presents a structure for maximum way of exit. This structure including tanks connected at every corner to minimize the dependency on ground water and reuse the rainwater. In order to avoid flood, minimum size of tanks has been calculated by proposed Tank Size Descriptor (TSD) algorithm with the help of actual rainfall data. With the help of TSD algorithm any expert system of civil engineering will be able to suggest a design of a flood free city using hexagonal shapes within the cellular automata.Â Â
Keywords: Hexagonal cell; Cellular Automata (CA); Urban Flood; Optimization and Pipeline design.